Adipose‐derived stromal cells for the reconstruction of a human vesical equivalent. (11th April 2013) - Rousseau, Alexandre; Fradette, Julie; Bernard, Geneviève; Gauvin, Robert; Laterreur, Véronique; Bolduc, Stéphane
Abstract: Despite a wide panel of tissue‐engineering models available for vesical reconstruction, the lack of a differentiated urothelium remains their main common limitation. For the first time to our knowledge, an entirely human vesical equivalent, free of exogenous matrix, has been reconstructed using the self‐assembly method. Moreover, we tested the contribution of adipose‐derived stromal cells, an easily available source of mesenchymal cells featuring many potential advantages, by reconstructing three types of equivalent, named fibroblast vesical equivalent, adipose‐derived stromal cell vesical equivalent and hybrid vesical equivalent – the latter containing both adipose‐derived stromal cells and fibroblasts. The new substitutes have been compared and characterized for matrix composition and organization, functionality and mechanical behaviour. Although all three vesical equivalents displayed adequate collagen type I and III expression, only two of them, fibroblast vesical equivalent and hybrid vesical equivalent, sustained the development of a differentiated and functional urothelium. The presence of uroplakins Ib, II and III and the tight junction marker ZO‐1 was detected and correlated with impermeability. The mechanical resistance of these tissues was sufficient for use by surgeons. We present here in vitro tissue‐engineered vesical equivalents, built without the use of any exogenous matrix, able to sustain mechanical stress and to support the formation of a functional urothelium, i.e. able to display a barrier function similar to that of native tissue. Copyright © 2013 John Wiley & Sons, Ltd.